(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The green economy is a transformative approach that seeks to align economic growth with environmental sustainability. This paper explores how developed countries have applied green economy principles and the resulting impacts on sustainability. By analyzing case studies from various regions, this study highlights key strategies, successes, and challenges in transitioning towards a more sustainable future.